Prevalence of Osteoporosis in Patients with Type 2 Diabetes Mellitus in the Chinese Mainland: A Systematic Review and Meta-Analysis - Yuhao SI; Cenyi WANG; Yang GUO; Guihua XU; Yong MA (Tehran University of Medical Sciences, 2019)
Background: Some studies have investigated the prevalence of osteoporosis in patients with type 2 diabetes mellitus (T2DM) in China. However, the results were inconsistent. This review was performed to estimate the prevalence of osteoporosis in T2DM patients in the Chinese mainland and to characterize its epidemiology. Methods: A literature search was conducted utilizing PubMed, Scopus, Web of Science, Cochrane Library, CNKI, Wanfang database from their inception through June 2017. A total of 54 studies evaluating the prevalence rate of osteoporosis in T2DM patients were collected. Prevalence estimates from the individual study were combined utilizing random-effect models in Stata 12.0. Results: The pooled prevalence rate of osteoporosis in T2DM patients was 37.8%. Notably, osteoporosis was more frequent in females than in males (44.8% vs. 37.0%) and was increased with ageing (over 60: 40.1% vs. below 60: 26.5%). Osteoporosis prevalence was higher in less developed areas than in developed areas (41.0% vs. 32.7%) and almost the same between the southern and northern regions (37.6% vs. 38.2%). The prevalence rate between 2010 and 2017 decreased compared with the period between 2001 and 2009 (42.3% vs. 35.6%). Additionally, the meta-regression suggested that gender and age could significantly influence the estimation of prevalence rates respectively (P = 0.011, P = 0.022). Conclusion: Osteoporosis affects more than one-third of T2DM patients in China mainland. Females and older adults more likely require clinical prevention due to a higher prevalence. Further studies are needed to be conducted to incorporate and verify previous results.